Studies on Monstereae (Araceae) of Borneo I : Two Novel Anadendrum from Sarawak - Peter C., Boyce; Wong S., Yeng (Sarawak Museum, 2010)
Two new Anadendrum from Sarawak, A. calciola and A. muluensis, are described and illustrated. By the leaf lamina abaxially glaucous they are most similar to A. affine (Sumatera). Anadendrum calcicola differs from A. affine in the bimodal gorgonoid synflorescence, and the stamen filaments not extending at male anthesis.